IP Cores Design from Specifications to Production Modeling, Verification, Optimization, and Protection - Mohamed, Khaled Salah; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book describes the life cycle process of IP cores, from specification to production, including IP modeling, verification, optimization, and protection. Various trade-offs in the design process are discussed, including  those associated with many of the most common memory cores, controller IPs  and system-on-chip (SoC) buses. Readers will also benefit from the author's practical coverage of new verification methodologies. such as bug localization, UVM, and scan-chain.  A SoC case study is presented to compare traditional verification with the new verification methodologies. ·         Discusses the entire life cycle process of IP cores, from specification to production, including IP modeling, verification, optimization, and protection; ·         Introduce a deep introduction for Verilog for both implementation and verification point of view.  ·         Demonstrates how to use IP in applications such as memory controllers and SoC buses. ·         Describes a new verification methodology called bug localization; ·         Presents a novel scan-chain methodology for RTL debugging; ·         Enables readers to employ UVM methodology in straightforward, practical terms.
1. Introduction -- 2. IP Cores Design from Specifications to Production: Modeling, Verification, Optimization, and Protection -- 3. Analyzing the Trade-off between Different Memory Cores and Controllers -- 4. SOC BUSES AND PERIPHERALS: FEATURES AND ARCHITECTURES -- 5. Verilog for Implementation and Verification -- 6. New Trends in SoC Verification: UVM, Bug Localization, Scan-Chain-Based Methodology, GA-Based Test Generation -- 7. Conclusions.
Keywords: Electronic circuits; Microprocessors; Computer architecture; Electronics; Electronic Circuits and Systems; Processor Architectures; Electronics and Microelectronics, Instrumentation